Meningococcal septicaemia and a case of clinically mild illness - Esler, Danielle M; Lewis, Peter R (Communicable Diseases Intelligence, 2007)
The advent of new investigations for the detection of invasive meningococcal disease may lead to the diagnosis of milder forms of the infection which would previously have remained undiagnosed. In the context of mild disease there may be difficulty interpreting current guidelines and subsequently formulating an appropriate management and public health plan. This case study demonstrates the issues that may arise when positive serology results become available for a person with either partially, or un-treated mild invasive meningococcaemia.